The retinal tyrosine kinome of diabetic Akimba mice highlights potential for specific Src family kinase inhibition in retinal vascular disease. (August 2020) - Sergeys, Jurgen; Van Hove, Inge; Hu, Tjing-Tjing; Temps, Carolin; Carragher, Neil O.; Unciti-Broceta, Asier; Feyen, Jean H.M.; Moons, Lieve; Porcu, Michael
Abstract: Although anti-VEGF therapies have radically changed clinical practice, there is still an urgent demand for novel, integrative approaches for sight-threatening retinal vascular diseases. As we hypothesize that protein tyrosine kinases are key signaling mediators in retinal vascular disease, we performed a comprehensive activity-based tyrosine kinome profiling on retinal tissue of 12-week-old Akimba mice, a translational model displaying hallmarks of early and advanced diabetic retinopathy. Western blotting was used to confirm retinal tyrosine kinase activity in Akimba mice. HUVEC tube formation and murine organotypic choroidal sprouting assays were applied to compare tyrosine kinase inhibitors with different specificity profiles. HUVEC toxicity and proliferation were evaluated using the CellTox™ Green Cytotoxicity and PrestoBlue™ Assays. Our results indicate a shift of the Akimba retinal tyrosine kinome towards a hyperactive state. Functional network analysis of significantly hyperphosphorylated peptides and upstream kinase prediction revealed a central role for Src-FAK family kinases. Western blotting confirmed hyperactivity of this signaling node in the retina of Akimba mice. We demonstrated that not only Src but also FAK family kinase inhibitors with different selectivity profiles were able to suppress angiogenesis in vitro and ex vivo . In the latter model, the novel selective Src family kinase inhibitor eCF506 was able to achieve potent reduction of angiogenesis, comparable to the less specific inhibitor Dasatinib. None of the tested compounds demonstrated acute endothelial cell toxicity. Overall, the collected findings provide the first comprehensive overview of retinal tyrosine kinome changes in the Akimba model of diabetic retinopathy and for the first time highlight Src family kinase inhibition using highly specific inhibitors as an attractive therapeutic intervention for retinal vascular pathology. Highlights: Retinal tyrosine kinome profiling reveals hyperactivity in diabetic Akimba mice. Functional network analysis identifies Src-FAK family kinases as central node. Specific Src family kinase inhibition potently suppresses ex vivo angiogenesis.